Teacher’s Techniques in Teaching Speaking at The Tenth Graders at MA Bustanul Ulum Tanggungprigel, Glagah, Lamongan - Wafiyah, Wafa; Shofi, Ahmad Thoyyib (Indonesian Journal of Multidisciplinary Educational Research, 2023)
This research is about teachers techniques in teaching speaking at the tenth graders at MA Bustanul Ulum. The aim of this research is to know the technique used by English teacher and students’ response in teacher’s techniques in teaching speaking at the tenth graders level of MA Bustanul Ulum. The challenges faced by teacher when applying techniques in teaching speaking include dealing with students who lack seriousness and consequently disrupt their peers. On the other hand, students encounter difficulties in the process of learning speaking due to the repetitive use of the same technique by the teacher. In collecting data, the researcher faced several problems, including teacher who often used repetitive activities when teaching speaking and uncooperative students. mastering English speaking is a crucial aspect of overall language proficiency. When it comes to learning to speak, it is essential for teachers to carefully select appropriate techniques that effectively can made students' comprehension and progress in acquiring spoken language skills. The design of the research was descriptive qualitative, which obtained the data through observations, and questionnaire. The researcher collected the data by observation and took field notes to know what technique the teacher used and how the teacher applied the technique in the teaching and learning process. The subjects of this research were an English teacher and students in the tenth grade. The researcher found that in teaching speaking, the teacher did not use any of the techniques that has mentioned by the researcher in this thesis on teaching speaking.